Mroczne żądło zdegenerowanej natury. Szkic o czarnoromantycznych inspiracjach Róży Wojciecha Smarzowskiego - SZPULAK, ANDRZEJ (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
The dark sting of degenerate nature. Sketch of the dark-romantic inspirations in Wojciech Smarzowski’s Rose The text presents Polish dark romanticism as an important source of inspiration for the images of violence, includ- ing sexual violence, in Wojciech Smarzowskis Rose. The author reveals the mechanisms of this inspiration: visual, dramatic, intellectual, and refers to specific literary texts, from the Romantic era and later, by Antoni Malczewski, Seweryn Goszczyński, Juliusz Słowacki and Włodzimierz Odojewski.